A systematic approach to efficiently managing the effects of retroactive updates of time-varying data in multiversion XML databases. (2018) - Hamrouni, Hind; Brahmia, Zouhaier; Bouaziz, Rafik
A retroactive update is an update that changes a past data. It is a common operation in both conventional and temporal databases. However, in temporal databases, a retroactive update is challenging since it could lead to data inconsistencies if the retroactively updated data were used for creating other data (like social contributions and taxes which are calculated based on the salaries of the employees). Such data inconsistencies must be repaired in order to preserve the database consistency. In this paper, we extend our previous approach on detecting and repairing automatically data inconsistencies that result from retroactive updates of multiversion temporal XML databases. The extension consists in: 1) providing an enhanced version of the architecture of our approach and explaining the process of handling a retroactive update; 2) showing how to extract data dependencies and how to use them in order to repair detected inconsistencies; 3) proposing a new log structure ensuring a complete and useful history of the executed transactions; 4) presenting a tool, named Retro-Update-Manager, that we have developed to prove technically our approach.